The importance of long-term social research in enabling participation and developing engagement strategies for new dengue control technologies. - Darlene McNaughton (Public Library of Science (PLoS), 2012)
BACKGROUND: In recent years, new strategies aimed at reducing the capacity of mosquito vectors to transmit dengue fever have emerged. As with earlier control methods, they will have to be employed in a diverse range of communities across the globe and into the main settings for disease transmission, the homes, businesses and public buildings of residents in dengue-affected areas. However, these strategies are notably different from previous methods and draw on technologies that are not without controversy. Public engagement and authorization are critical to the future success of these programs. METHODOLOGY/PRINCIPAL FINDINGS: This paper reports on an Australian case study where long-term social research was used to enable participation and the design of an engagement strategy tailored specifically to the sociopolitical setting of a potential trial release site of Wolbachia-infected Aedes aegytpi mosquitoes. Central themes of the social research, methods used and conclusions drawn are briefly described. Results indicate that different communities are likely to have divergent expectations, concerns and cultural sensibilities with regard to participation, engagement and authorization. CONCLUSIONS/SIGNIFICANCE: The findings show that a range of issues need to be understood and taken into account to enable sensitive, ethical and effective engagement when seeking public support for new dengue control methods.